Conditions and characteristics of droplets breakup for industrial waste-derived fuel suspensions ignited in high-temperature air; Fuel; Vol. 265 - Glushkov D. O. Dmitry Olegovich; Feoktistov D. V. Dmitriy Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Batishcheva K. A. Kseniya Arturovna; Kudelova T. Tereza; Paushkina K. K. Kristina Konstantinovna (2020, 2020)
Title screen